Epidemiological Characteristics and Maternal Risk Factors of Microtia and Aural Atresia in Kazakhstan - Imangaliyeva, Assel; Suatbayeva, Rimma; Slazhneva, Tatyana; Medeulova, Aigul; Mukanova, Zhanetta; Kulimbetov, Amangeldy; Mileshina, Neilya; Glushkova, Natalya; Izmailovich, Marina; Semenova, Yuliya (International Archives of Otorhinolaryngology, 2025)
Introduction Microtia and aural atresia present congenital ear anomalies that affect external ear and are associated with conductive hearing loss. Both anomalies result from exposure to various prenatal risk factors, most common during the first trimester of pregnancy.Objective This study was aimed at epidemiological analysis of microtia/atresia and associated risk factors in the Kazakhstani population.Methods A retrospective study in two stages. First, a cross-sectional analysis of microtia/ atresia frequencies from 2015 to 2019 on the basis of official statistics obtained from the Republican Centre for E-Health. Then, a case-control study was carried out to elucidate maternal risk factors associated with occurrence of microtia/atresia. We recruited patients presented in Almaty, Kazakhstan, between September 2021 and February 2022.Results There was a substantial regional variation in the rates of both aural atresia and microtia/anotia. Mothers of children with microtia disclosed toxoplasmosis, other agents (including HIV, syphilis, varicella), rubella, cytomegalovirus, herpes simplex (TORCH) infections during pregnancy more often than those of healthy children (45.8 versus 7.3%; p < 0.001). Exposure to different chemicals during pregnancy was mentioned more frequently by mothers of children with microtia when compared with the healthy controls (18.1 versus 8.1%; p = 0.035). Self-reporting of alcohol consumption and intake of antibiotics was also significantly higher in mothers of children with microtia (31.9 and 36.1% respectively).Conclusion Elucidation of microtia/atresia epidemiology is important due to their imposed social and economic burden, associated with treatment and rehabilitation costs.
Keywords: microtia; children; frequency; risk factors; meatal atresia